Author's reply to "comments on 'variable explicit regularization in affine projection algorithm: Robustness issues and optimal choice'" - Rey, Hernan Gonzalo (2010)
Muralidhar et al. point out that when the VR-APA is applied in echo cancellation it will diverge during the presence of a near-end signal or a silence period. We provide an explanation for the behavior of the algorithm and show that a double-talk detector makes the VR-APA suitable for this application.